Challenges to Exploring the Patient Perspective in Palliative Care Conversations: A Qualitative Study Among Chronic Obstructive Pulmonary Disease and Chronic Heart Failure Patients and Their Health Care Professionals - Annet Olde Wolsink-van Harlingen; Leontine Groen-van de Ven; Kris Vissers; Jeroen Hasselaar; Jan Jukema; Madeleen Uitdehaag (Palliative Medicine Reports, 2024)
Objectives: The aim of this study was to reveal the challenges faced in exploring the patient's perspective as experienced by patients with chronic obstructive pulmonary disease or chronic heart failure and their health care professionals (HCPs), including the circumstances under which these challenges are experienced during palliative care conversations. Methods: This is a qualitative, explorative study in the Netherlands using purposive sampling to create diversity in demographic variables of both patients and HCPs. Semistructured interviews with 12 patients and 7 HCPs were carried out with the use of topic lists. All interviews were audiorecorded, verbatim transcribed, and thematically analyzed. Results: Patients find it challenging to express their wishes, preferences, and boundaries and say what is really preoccupying them, especially when they do not feel a good connection with their HCP. HCPs find it challenging to get to know the patient and discuss the patient's perspective particularly when patients are not proactive, open or realistic, or unable to understand or recall information. Conclusions: Patients and HCPs seem to share the same aim: patients want to be known and understood and HCPs want to know and understand the patient as a unique individual. At the same time, they seem unable to personalize their conversations. To move beyond this impasse patients and HCPs need to take steps and be empowered to do so.